Tuberculosis drug streptomycin as a potential cancer therapeutic: inhibition of miR-21 function by directly targeting its precursor - Bose, Debojit; Jayaraj, Gopal Gunanathan; Suryawanshi, Hemant; Agarwala, Prachi; Pore, Subrata Kumar; Banerjee, Rajkumar; Maiti, Souvik (Angewandte Chemie-International Edition, 2012)
Keywords: Apoptosis; drug discovery; Gene expression; inhibitors; RNA

Molecular-beacon-based screen for small molecule inhibitors of miRNA maturation - Bose, Debojit; Jayaraj, Gopal Gunanathan; Kumar, Santosh; Maiti, Souvik (ACS Chemical Biology, 2013)
miRNAs are small non-coding RNAs that regulate about 60% of mammalian genes by modulating their transcript levels. Network scale studies of miRNA-mediated regulatory circuits demonstrate the central importance of this class of small RNA in the maintenance of biological robustness. More recently, several reports have described the deregulation of numerous miRNA to be causally associated with many diseases, including cancer. These studies have highlighted the potential for development of therapeutic modalities against miRNA. Previous screening protocols, for small molecules targeting miRNA function, are either costly or technically too complex to be applied in a high-throughput manner in standard chemical laboratories. We describe a simple in vitro screening method using a DNA-based molecular beacon that overcomes the limitations associated with earlier screens. We used this method to identify inhibitors of miR-27a function from a library of 14 aminoglycosides as a pilot study. Inhibitory molecules identified were further scrutinized to identify the validity of screen. With this proof of concept we illustrate the utility of a scalable molecular-beacon-based screening strategy for miRNA inhibitors.

Nonconventional chemical inhibitors of microRNA: therapeutic scope - Jayaraj, Gopal Gunanathan; Nahar, Smita; Maiti, Souvik (Chemical Communications, 2015)
MicroRNAs (miRNAs) are a class of genomically encoded small RNA molecules (similar to 22nts in length), which regulate gene expression post transcriptionally. The term microRNA or miRNA was coined in 2001, and research in the past decade has shed light on their widespread occurrence, evolutionary conservation and tissue specific functions. It is estimated that they modulate the gene expression of approximately 60% of the mammalian genes by regulating the levels of target mRNAs to which they can bind on the basis of sequence complementarities. miRNAs are produced in a well coordinated series of steps from being transcribed in the nucleus to exerting their function in the cytoplasm. miRNAs are now implicated in diverse biological phenomena ranging from development to stress response which makes miRNAs one of the central regulatory molecules which modulate information flow along the central dogma of gene expression. More importantly, like any regulatory molecule, deregulation of miRNAs is causally associated with several diseases (mainly cancer) and is directly involved in a variety of pathophysiologies owing to their aberrant expression. Thus, modulation of miRNA levels is of prime therapeutic importance. Conventional methods of miRNA knockdown using chemically modified antisense-oligonucleotides have been explored extensively but face the challenges of modes of delivery, biostability and biodistribution. This calls for the development of more alternative and non-conventional methods to target miRNA. Small molecules targeting RNA chemical and structural space provide one such timely opportunity. In this article we first provide a brief overview of miRNA biogenesis and its disease associations. We then summarize the major developments in conventional oligonucleotide based approaches to miRNA knockdown and its status. We then focus on the more non-conventional methods like oligonucleotide enzymes and small molecules and provide an outlook on the future of such methods.

RNA stem-loop to G-quadruplex equilibrium controls mature MicroRNA production inside the cell - Pandey, Satyaprakash; Agarwala, Prachi; Jayaraj, Gopal Gunanathan; Gargallo, Raimundo; Maiti, Souvik (Biochemistry, 2015)
The biological role of the existence of overlapping structures in RNA is possible yet remains very unexplored. G-Rich tracts of RNA form G-quadruplexes, while GC-rich sequences prefer stem-loop structures. The equilibrium between alternate structures within RNA may occur and influence its functionality. We tested the equilibrium between G-quadruplex and stem-loop structure in RNA and its effect on biological processes using pre-miRNA as a model system. Dicer enzyme recognizes canonical stem-loop structures in pre-miRNA to produce mature miRNAs. Deviation from stem-loop leads to deregulated mature miRNA levels, providing readout of the existence of an alternate structure per se G-quadruplex-mediated structural interference in miRNA maturation. In vitro analysis using beacon and Dicer cleavage assays indicated that mature miRNA levels depend on relative amounts of K+: and Mg2+ ions, suggesting an ion-dependent structural shift. Further in cellulo studies with and without TmPyP4 (RNA G-quadruplex destabilizer) demonstrated that miRNA biogenesis is modulated by G-quadruplex to stem-loop equilibrium in a subset of pre-miRNAs. Our combined analysis thus provides evidence of the formation of noncanonical G-quaciruplexes in competition with canonical stem-loop structure inside the cell and its effect on miRNA maturation in a comprehensive manner.